2008
DOI: 10.1109/twc.2008.060545
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Based TOA Estimation

Abstract: This paper investigates time of arrival estimation via impulse radio ultra-wideband technology. A dense multipath channel is assumed and frequency-selective propagation effects are taken into account that make the individual received pulses different in shape from the transmitted monocycles. In these conditions a conventional correlation-based estimator cannot be used and other schemes must be resorted to. Assuming only an approximate knowledge of the received pulses’ duration, a TOA estimator is deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…It is shown that only one iteration is needed to achieve the lower bound at high SNRs. The reason is that the improvement in MSE depends on the reliability of data detection results as derived in (22). At extremely low SNRs, the SER of iterative estimator is significantly high such that the data-aided method can be deteriorated by the large portion of data decision errors.…”
Section: Performance Of the Joint Iterative Estimatormentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that only one iteration is needed to achieve the lower bound at high SNRs. The reason is that the improvement in MSE depends on the reliability of data detection results as derived in (22). At extremely low SNRs, the SER of iterative estimator is significantly high such that the data-aided method can be deteriorated by the large portion of data decision errors.…”
Section: Performance Of the Joint Iterative Estimatormentioning
confidence: 99%
“…For real applications with complexity constraints, several simple techniques have been proposed to detect the first path. Energy detection-based method was proposed in [20][21][22][23]. However, the energy detector can perform poorly when the strength of the first path is not the strongest one.…”
Section: Introductionmentioning
confidence: 99%
“…3, τ h exceeds τ by some quantity ∆, i.e., τ h = τ + ∆. In the second step (leading-path search) we start from the highest peak already found and, as in [5], we jump back by T back seconds to an instant prior to the beginning of the q(t)-pulse. Then, we perform a forward search looking for the first appearance of the q(t)-pulse energy.…”
Section: Time Domain Toa Estimationmentioning
confidence: 99%
“…Many TOA estimators have been proposed in the literature, especially for impulse radio UWB (IR-UWB) signals. Most proposed estimators like the maximum likelihood estimator (MLE), the energy-based estimators, the autocorrelation-based estimators, the threshold-based estimators, and others are based on the time domain [2][3][4][5][6][7][8][9][10]. The drawback of time-domain estimators is that their precision is limited by the sampling frequency being used, and complex interpolation is required in order to improve the performance.…”
Section: Introductionmentioning
confidence: 99%